The impact of in-work benefits on female labor supply and income distribution in Spain - Luis Ayala Ca\~nón; Milagros Paniagua (University of Essex, Institute for Social and Economic Research (ISER), 2017)
In-work benefits (IWBs) have become very common transfer programs that seek to meet both efficiency and equity targets. An expanding literature has assessed the effects of these policies on income distribution and labor supply showing important implications for female labor participation. In this paper, we estimate the distributional and behavioral impacts of a simulated IWB in Spain based on the replacement of the existing working mother tax credit (WMTC) using as a reference the US Earned Income Tax Credit (EITC). We simulate the effects of the proposed scheme using EUROMOD and a discrete choice model of labor supply. Our results show that the enhancement of the proposed IWB would have significant and positive effects both in terms of female labor participation and inequality and poverty reduction. The introduction of this IWB would generate a substantial increase in labor participation at the extensive margin and a non-negligible reduction at the intensive margin.
Keywords: I38; H23; J22; 330; in-work benefits; female labor supply; microsimulation; EITC; EUROMOD